2016
DOI: 10.25159/0027-2639/844
|View full text |Cite
|
Sign up to set email alerts
|

€˜I DON’T WANT TO BE CARRIED LIKE LUGGAGE’: DISABILITY AND PHYSICAL ACCESS TO TANZANIAN ACADEMIC LIBRARIES

Abstract: This article reports on an empirical study which investigated access for people in wheelchairs and/or with visual impairments to Tanzanian academic libraries. A pragmatism paradigm and Oliver’s (1990) social model of disability were employed as well as the International Classification of Functioning, Disability and Health (ICF). Using quantitative and qualitative methods, questionnaires, interview schedules and an observation checklist were used to collect data. The study sample from the libraries of five Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Conversely, a current key survey in a developed country showed that most PWDs who participated did not have difficulties accessing public buildings (UK Government Disability Unit, 2021). Evidence from other nations about PWDs, regardless of their functional ability, having to be manually assisted or moved due to deficient facilities in public buildings (Banda-Chalwe et al, 2013;Majinge and Stilwell, 2015;Peterson, 2021) offers an explanation for our finding, as such a situation decreases their independence. In addition, indigenous data reveal that many Nigerian PWDs are unable to use public buildings' facilities by themselves (Jirgba et al, 2020;Sholanke et al, 2019;Soyingbe et al, 2017), which further corroborates our finding of a low level of independence.…”
Section: Level Of Independencementioning
confidence: 66%
See 2 more Smart Citations
“…Conversely, a current key survey in a developed country showed that most PWDs who participated did not have difficulties accessing public buildings (UK Government Disability Unit, 2021). Evidence from other nations about PWDs, regardless of their functional ability, having to be manually assisted or moved due to deficient facilities in public buildings (Banda-Chalwe et al, 2013;Majinge and Stilwell, 2015;Peterson, 2021) offers an explanation for our finding, as such a situation decreases their independence. In addition, indigenous data reveal that many Nigerian PWDs are unable to use public buildings' facilities by themselves (Jirgba et al, 2020;Sholanke et al, 2019;Soyingbe et al, 2017), which further corroborates our finding of a low level of independence.…”
Section: Level Of Independencementioning
confidence: 66%
“…Finally, our study revealed that lack of amenities was the primary challenge encountered by PWDs. This denotes the absence of barrier-free facilities in public buildings, which has been highlighted by several authors in different countries (Abdul Kadir and Jamaludin, 2012; Banda-Chalwe et al , 2013; Gladstone, 2015; Majinge and Stilwell, 2015). Multiple Nigerian authors also agree that there is a great dearth of such facilities in local public buildings (Ahmed et al , 2014; Ibem et al , 2017; Sholanke et al , 2019), especially elevators (Bumma et al , 2020), signage (Soyingbe et al , 2017) and modified toilets (Babalola et al , 2020).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation